Electron transfer via CoO coupled to NPC derived from N, P-rich Chlorella pyrenoidosa enhanced radical-nonradical process in catalytic ozonation for efficient ibuprofen removal - Wei, Xingyue; Zhang, Hanmin; Cao, Mengbo (Chemical engineering journal (Lausanne, Switzerland : 1996), 2024)
[Display omitted] •CoO dispersed on NPC derived from Chlorella was constructed by one-step pyrolysis.•The coupling of CoO and NPC catalyzes ozone to remove 99.9 % of IBU in 30 min.•OH and *O were the main active species in 2Co-NPC HCO process.•C-O-Co and C-N-Co accelerated electron transfer during HCO process.•Electron-rich Co(II) center is active sites for efficient ozone decomposition. In this study, a series of Co-doped NPC biochar (nCo-NPC) was prepared by one-step pyrolysis of N and P-rich Chlorella pyrenoidosa (CP) waste mixed with cobalt nitrate for heterogeneous catalytic ozonation (HCO) degradation of ibuprofen (IBU). Compared to the HCO process using CoOx or NPC catalysts, the 2Co-NPC catalyst showed superior performance in the degradation of IBU due to the synergistic effect between the CoOx and NPC. The 2Co-NPC catalyst exhibited high stability after five trials, with the removal efficiency decreasing from 99.9 % to 85.4 %. Moreover, hydroxyl radicals (OH) and adsorbed atomic oxygen (*O) were identified as the main active species in 2Co-NPC HCO process. The coupling of NPC and CoOx formed electron-rich Co(II) center and electron-deficient NPC center. The electron-rich Co(II) center can direct decomposition of adsorbed ozone into *O and further convert to OH. The electron-deficient NPC center gained electrons from organic pollutants, CN, CO, and P groups through COCo and CNCo bonds, stimulating the π-cation reaction to transfer to the Co(II) center, thus accelerating the cycling between Co(II) and Co(III). Additionally, the deprotonation of surface hydroxyl groups may also serve as a potential active site for the decomposition of ozone into OH. This study used biomass CP as a precursor coupled with cobalt salt, revealing electron transfer pathways and providing new insights for the future developing of low-cost, efficient, and stable ozone catalysts.